Effect of Cooling Conditions, Retrofitting on Strength of Concrete Subjected to Elevated Temperature - Swapnil B. Kharmale; Pramod S. Sathe; Yashwant A. Kolekar (Salehan Institute of Higher Education, 2023)
Concrete has a high degree of fire resistance at moderate temperatures. High temperatures, however, cause concrete to lose its stiffness and strength. The effects of cooling techniques and retrofitting on the strength of concrete exposed to high temperatures have not been synchronized in previous studies. This experimental research aims to evaluate the effect of cooling conditions and the effectiveness of retrofitting concrete subjected to elevated temperatures. Four types of concrete: M 20 normal concrete (NC); M 20 metakaolin concrete (MC); M 40 standard concrete (SC); and M 40 self-compacting concrete (SCC) are considered in this study. A total of 864 samples consisting of cube, beam, and cylinder specimens are subjected to sustained elevated temperatures of 400oC, 600oC, and 800oC for 2 hours rating. The weight and strength of half of the heat-damaged samples are assessed following natural air cooling (NAC) and water jet cooling (WJC). The remaining 50% of samples retrofitted with carbon fiber reinforced polymer (CFRP) are tested to evaluate the upgraded strength. The experimental findings demonstrate that water jet cooling (WJC) causes more strength degradation, and CFRP proves to be effective in restoring the strength of heat-deteriorated specimens. Overall, self-compacting concrete (SCC) has shown high resistance to elevated temperatures.Â Doi: 10.28991/CEJ-2023-09-07-013 Full Text: PDF